Phase I study of palbociclib, a cyclin‐dependent kinase 4/6 inhibitor, in Japanese patients. Issue 6 (11th May 2016) - Tamura, Kenji; Mukai, Hirofumi; Naito, Yoichi; Yonemori, Kan; Kodaira, Makoto; Tanabe, Yuko; Yamamoto, Noboru; Osera, Shozo; Sasaki, Masaoki; Mori, Yuko; Hashigaki, Satoshi; Nagasawa, Takashi; et al.
Abstract : This phase I study in Japanese patients evaluated the safety, pharmacokinetics, and preliminary efficacy of palbociclib, a highly selective and reversible oral cyclin‐dependent kinase 4/6 inhibitor, as monotherapy for solid tumors (part 1) and combined with letrozole as first‐line treatment of postmenopausal patients with estrogen receptor‐positive, human epidermal growth factor receptor 2‐negative advanced breast cancer (part 2). Part 1 evaluated palbociclib 100 and 125 mg once daily (3 weeks on/1 week off; n = 6 each group) to determine the maximum tolerated dose. Part 2 evaluated palbociclib maximum tolerated dose (125 mg) plus letrozole 2.5 mg ( n = 6). The most common treatment‐related adverse event was neutropenia (all grades/grade 3/4): 100 mg, 83%/67%; 125 mg, 67%/33%; and palbociclib plus letrozole, 100%/83%. Heavier pretreatment with chemotherapy may have resulted in higher neutropenia rates observed with the 100‐mg dose. Palbociclib exposure was higher with 125 vs 100 mg (mean area under the plasma concentration–time curve over dosing interval [τ]: 1322 vs 547.5 ng·h/mL [single dose], 2838 vs 1276 ng·h/mL [multiple dose]; mean maximum plasma concentration: 104.1 vs 41.4 ng/mL [single dose], 185.5 vs 77.4 ng/mL [multiple dose]). Half‐life was 23–26 h. No drug–drug interactions between palbociclib and letrozole occurred. Four patients had stable disease (≥24 weeks in one patient with rectal cancer [100 mg] and one with esophageal cancer [125 mg]) in part 1; two patients had partial response and two had stable disease (both ≥24 weeks) in part 2. Palbociclib at the 125‐mg dose (schedule 3/1) was tolerated and is the recommended dose for monotherapy and letrozole combination therapy in Japanese patients. The trials are registered withwww.ClinicalTrials.gov : A5481010 and NCT01684215. Abstract : This phase 1 study in Japanese patients evaluates the safety, pharmacokinetics, and preliminary efficacy of palbociclib as monotherapy for solid tumors (part 1) and combined with letrozole as first‐line treatment of postmenopausal patients with ER+/HER2− advanced breast cancer (part 2). Overall, the results of this study suggest that palbociclib 125 mg was tolerated and is a recommended dose for monotherapy and letrozole combination therapy in Japanese patients.